Intelcity and multiple criteria web-based negotiation decision support system for real estate - Kaklauskas, Artūras; Urbanavičienė, Vita (Technological and Economic Development of Economy, 2005)
The authors of this paper together with the other VGTU scientists participate in the international project INTELCITIES and present Multiple Criteria Web‐Based Negotiation Decision Support System for Real Estate (NDSSRE). INTELCITIES project is a research and development project that aims to pool advanced knowledge and experience of e‐government, planing systems and citizen participation. NDSS‐RE includes a decision support tool based on the methods of alternative generation and multiple criteria analysis that enable negotiating parties to evaluate their systems of preferences and recognize opportunities for trade‐off between differently valued objectives and joint gains. At present the developed NDSS‐RE allows for the performance of the following functions: search for real estate alternatives; finding out alternatives and making an initial negotiation table; multiple criteria analyses of alternatives; negotiation based on real calculations; determination of the most rational real estate purchase variant on the ground of characteristics describing effectiveness of the analysed alternatives. The third part of the paper deals with traditional negotiation principles and describes negotiation tactics, such as “The Atractive Alternative”, “The Stall and Jolt”, “The Comparative Value”, “The Third Party”, “The No More Money” and “The Walk Away” tactics. More traditional negotiation principles and tactics have been planned to integrate in future concerning the described NDSS‐RE system because the knowledge and implementation of all the above mentioned tactics and principles lead to more successful negotiation for the lowest possible price buying real estate. Article in Lithuanian. Intelektualus miestas ir internetinė nekilnojamojo turto daugiakriterinė derybinė sprendimų paramos sistema Santrauka. Straipsnio autoriai kartu su kitais VGTU mokslininkais dalyvauja tarptautiniame projekte „INTELCITIES“ ir pristato internetinę nekilnojamojo turto daugiakriterinę derybinę sprendimų paramos sistemą (NT-DSPS). „INTELCITIES“ projekto tikslas - sujungti elektroninės vyriausybės ir planavimo sistemų pažangias žinias bei patirtį ir skatinti miesto gyventojus naudotis elektroninėmis paslaugomis. Internetinėje nekilnojamojo turto daugiakriterinėje derybinėje sprendimų paramos sistemoje naudojami alternatyvų sudarymo, daugiakriterinės analizės ir derybų moduliai, kurie besiderančioms šalims leidžia adekvačiau įvertinti savo poreikius ir galimybes bei suprasti kompromiso galimybes pasiekti abipusiam išlošiui. NT-DSPS leidžia atlikti tokias funkcijas: nekilnojamojo turto alternatyvų paieška, alternatyvų suradimas ir pirminės lyginamosios lentelės sudarymas, daugiakriterinė alternatyvų analizė; realiais elektroniniais skaičiavimais pagrįstos derybos; efektyviausio nekilnojamojo turto pirkimo varianto nustatymas. Trečioje straipsnio dalyje aprašomi tradicinių nekilnojamojo turto derybų principai ir ÑPatrauklios alternatyvosì, ÑVilkinimo ir sukrėtimoì, „Lyginamosios vertės“, „Trečiosios šalies“, „Nėra daugiau pinigų“ bei „Pasitraukimo“ taktikos. Ateityje planuojama į NT-DSP sistemą įdiegti daugiau tradicinių derybų principų, kadangi visų straipsnyje nagrinėjamų pagrindinių derybų principų ir taktikų išmanymas bei pritaikymas leidžia pirkėjui sėkmingai derėtis dėl mažesnės nekilnojamojo turto kainos. Reikšminiai žodžiai: intelektualus miestas, daugiakriterinė internetinė nekilnojamojo turto derybinė sprendimų paramos sistema, nekilnojamojo turto derybų taktikos. First Published Online: 21 Oct 2010